Choosing a System of Unemployment Income Support : Guidelines for Developing and Transition Countries - Vodopivec, Milan (Oxford University Press on behalf of the World Bank, 2013)
Mounting evidence suggests that excessive job protection reduces employment and labor market flows, hinders technological innovations, pushes workers into the informal sector, and hurts vulnerable groups by depriving them of job opportunities. Flexible labor markets stimulate job creation, investment, and growth, but they create job insecurity and displace some workers. How can the costs of such insecurity and displacements be minimized while ensuring that the labor market remains flexible? Each of the main unemployment income support systems (unemployment insurance, unemployment assistance, unemployment insurance savings accounts, severance pay, and public works) has strengths and weaknesses. Country-specific conditions, chief among them labor market and other institutions, the capacity to administer each type of system, and the size of the informal sector, determine which system is best suited to developing and transition countries.